Предмет: Алгебра, автор: golubevn344

6) 4y¹ -(-5y¹-2y³) - (9y¹ - 2y³ - 1) пpи y = -0,5. ​

Ответы

Автор ответа: maymr
0

Ответ:

0,5

Объяснение:

\tt\displaystyle 4y-(-5y-2y^{3})-(9y-2y^{3}-1)=\\\\=4y+5y+2y^{3}-9y+2y^3+1=\\\\=9y+2y^3-9y+2y^3+1=\\\\=4y^3+1

при у = -0,5

\tt\displaystyle 4*(-0,5)^3+1=\\\\\\=4*(-\frac{5}{10})^3+1=\\\\\\=4*(-\frac{5^3}{10^3})+1=\\\\\\= 4*(-\frac{125}{1000})+1=\\\\\\=-4*0,125+1=\\\\=-0,5+1=\\\\=\bold{0,5}

Похожие вопросы
Предмет: Химия, автор: vanyaaleksandrov0303